Aurora-A inactivation causes mitotic spindle pole fragmentation by unbalancing microtubule-generated forces - Asteriti, Italia A (BioMed Central, 2011)
BACKGROUND: Aurora-A is an oncogenic kinase playing well-documented roles in mitotic spindle organisation. We previously found that Aurora-A inactivation yields the formation of spindles with fragmented poles that can drive chromosome mis-segregation. Here we have addressed the mechanism through which Aurora-A activity regulates the structure and cohesion of spindle poles. RESULTS: We inactivated Aurora-A in human U2OS osteosarcoma cells either by RNA-interference-mediated silencing or treating cultures with the specific inhibitor MLN8237. We show that mitotic spindle pole fragmentation induced by Aurora-A inactivation is associated with microtubule hyperstabilisation. Silencing of the microtubule-stabilising factor ch-TOG prevents spindle pole fragmentation caused by inactivation of Aurora-A alone and concomitantly reduces the hyperstabilisation of microtubules. Furthermore, decreasing pole-directed spindle forces by inhibition of the Eg5 kinesin, or by destabilisation of microtubule-kinetochore attachments, also prevents pole fragmentation in Aurora-A-inactivated mitoses. CONCLUSIONS: Our findings indicate that microtubule-generated forces are imbalanced in Aurora-A-defective cells and exert abnormal pressure at the level of spindle poles, ultimately causing their fragmentation. This study therefore highlights a novel role of the Aurora-A kinase in regulating the balance between microtubule forces during bipolar spindle assembly.